Preservice Teachers' Community-Based Field Experiences - Hamilton, Erica R.; Margot, Kelly C. (Frontiers in Education, 2019)
There exists much potential for the use of community-based partnerships to support preservice teachers’ learning and development. These opportunities can also expand preservice teachers’ understanding of when and where teaching and learning take place. This paper reports the results of a qualitative, yearlong pilot study focused on secondary preservice teachers’ (N=42) weekly community-based field experiences at a newly opened secondary public museum school, located in a large Midwestern urban area. Specifically, preservice teachers worked weekly with sixth grade students in an urban public museum setting as part of a required undergraduate content area literacy teacher education course. This study highlights ways this community-based field experience served as an important clinical component for preservice teacher learning. Working in this community-based setting provided expanded and varied opportunities for preservice teacher learning, including practice using and facilitating small group instruction and opportunities to support adolescents’ learning through accessing, exploring, and examining museum artifacts and exhibits. Therefore community-based field experiences, when and where feasible, may serve as an important clinical component for preservice teacher learning.